2001
DOI: 10.1159/000046283
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A Nephropathy and Ulcerative Colitis

Abstract: The immune response has largely been implicated in the pathogenesis of inflammatory bowel disease (ulcerative colitis and Crohn’s disease) and immunoglobulin A nephropathy. We present a 26-year-old woman with a long past history of asymptomatic macroscopic hematuria who later developed several episodes of bloody stools and abdominal pain. A colonic biopsy disclosed ulcerative colitis and a renal biopsy was consistent with immunoglobulin A nephropathy. Immunoglobulin A nephropathy is the most common glomerulone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…They described both clinical and pathologic remission of kidney disease concomitant with the treatment of symptoms of intestinal disease. Nineteen subsequent case reports in the literature have described IgAN in IBD (9,22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A majority of these patients had IgAN during onset or exacerbation of IBD, as well as clinical remission of kidney disease in conjunction with successful treatment of bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…They described both clinical and pathologic remission of kidney disease concomitant with the treatment of symptoms of intestinal disease. Nineteen subsequent case reports in the literature have described IgAN in IBD (9,22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A majority of these patients had IgAN during onset or exacerbation of IBD, as well as clinical remission of kidney disease in conjunction with successful treatment of bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Renal and genitourinary tract manifestations are quite rare in IBD, especially glomerulonephritis. Some renal involvements reported in IBD are aminosalicylate-related interstitial nephritis and IgA nephropathy (10)(11)(12)(13). In literature review, only one case of mesangial IgMN associated with UC has been de- scribed (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we found seven reports of IgAN in Crohn's disease [8][9][10][11][12][13][14][15], five reports in ulcerative colitis [16][17][18][19][20], and one report of IgAN with circulating immune complexes containing IgA in inflammatory bowel disease [21]. These reports described a total of 15 patients.…”
Section: Discussionmentioning
confidence: 99%